Developing strategies to facilitate the motivation of nurses rendering quality patient care in rural hospitals : an appreciative inquiry approach - Mulaudzi, Fhumulani Mavis (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.